Optimization of aggregate's packing density in the strength's improvement of OPC concrete - Siti Dalila, Ruslan (2014)
The purpose of this study was to determine the optimum packing density, workability and the strength of the concrete. Mix of concrete is made from OPC and granite aggregates, sand and water with different quantities of aggregates. Simulation graph are made in advance to determine the quantity of aggregates required for each mix. Diameter of the aggregates used for each mixture is between 20mm, 14mm, 10mm, and 5mm. The mixing is done as normal concrete with different aggregates for each diameter. The workability test of the concrete will be done after the mix is done to determine whether the concrete reaches the design was done which is a drop of 100cm. If the drop of concrete did not reach 100cm, the workability of concrete is not exceeded desired design and mixing must be performed again by adding the amount of water as the mixture is too dry. Mixture is left for 24 hours before being released from the box shape and cured. For this study, the concrete cured in a pool filled with water. Strength tests will be carried out at 1, 7, and 28 days. The results of the tests conducted, the strength of concrete is made to achieve the design of 30Mpa for each cube.